Prevalence and public health relevance of enteric parasites in domestic dogs and cats in the region of Madrid (Spain) with an emphasis on Giardia duodenalis and Cryptosporidium sp. (2023)
ABSTRACT: Background: Pet dogs and cats exert an unquestionable beneficial effect in the well-being of their owners, but can also act as a source of zoonotic infections if improperly cared. Objectives: We investigated the occurrence, risk factors, genetic variability and zoonotic potential of intestinal parasites in dogs and cats attended in a clinical veterinary setting in Spain. Methods: Canine (n = 252) and feline (n = 35) faecal samples were collected during 2017-2019 and analysed by coproparasitological methods. A rapid lateral immunochromatographic test (ICT) was used for detecting Giardia duodenalis and Cryptosporidium sp. Samples positive at microscopy examination and/or ICT were reassessed by molecular methods. Results: Overall, 48.8% (123/252) of dogs and 48.6% (17/35) of cats were infected by enteric parasites. In dogs, G. duodenalis was the most prevalent species (40.9%), followed by Cystoisospora sp. (7.1%), and Toxocara canis (5.2%). In cats, Joyeuxiella sp. and Toxocara cati were the dominant species (20.0% each), followed by G. duodenalis (14.3%), D. caninum (5.7%) and Cystoisospora felis and Toxascaris leonina (2.9% each). Pups and kittens were more likely to harbour intestinal parasites and develop clinical signs. Sequence analyses of dog isolates revealed the presence of assemblages A (n = 1), C (n = 4), D (n = 4) and C+D (n = 1) within G. duodenalis; C. parvum (n = 1) and C. canis (n = 4) within Cryptosporidium and PtEb IX (n = 1) in Enterocytozoon bieneusi. A novel C. canis subtype family, named XXi, is reported. Conclusions: Our results highlight that (i) well-cared dogs carry zoonotic enteric protozoan parasites of public health relevance, (ii) proper hygiene practices and routine veterinary treatment are essential to prevent zoonotic infections, (iii) vulnerable populations should avoid contact with pups/kittens with diarrhoea and (iv) infected dogs might be major contributors to the environmental contamination with soil-transmitted helminths (STHs) eggs. Keywords: genotyping; helminths; prevention; protists; small animal clinic; transmission; zoonosis.